Futur anxiety and its reationship to gender and academic specialization variables among Final secondary school- a field study on a sample in final departement in Secondary school Relizane province-Algerie- - Chaanebi, Noreddine; Balaalia, Mohammed (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The current study aims to know the level of future anxiety among students of the final secondary school in the province of Relizane, and to reveal the differences in the level of future anxiety due to gender and academic specialization. In order to achieve the purposes of this study the researcher use the measure of future anxiety was applied on random sample of 150 students. After processing the data using the 20 spss program, the following general results have been reached: - There is a middel level of future anxiety among students in the final sections of the secondary stage.- There are statistically significant differences in the level of future anxiety among the sample according to the gender variable.- There are statistically significant differences in the level of future anxiety among students of the final sections of the secondary stage according to the variable of the academic specialization (experimental sciences, mathematical technique and literature of philosophy)